UV/EB Cure Mechanism for Porous PECVD/SOD Low-k SiCOH Materials - Nakao, S.-I.; Ushio, J.; Ohno, T.; Hamada, T.; Kamigaki, Y.; Kato, M.; Yoneda, K.; Kondo, S.; Kobayashi, N. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
The mechanism of UV and EB cure processes for porous low-k SiCOH materials was investigated by using experimental results obtained using PECVD and SOD films as well as simulated results. Both UV and EB cures induced dielectric constant change and Young's modulus improvement because Si-OH elimination (moisture removal) and cross-link formation occurred during film shrinkage. Excess UV curing, however, caused defects in the porous SiCOH film, as indicated by ESR analysis. The mechanism discussed in this work is applicable to most UV/EB cure systems and PECVD/SOD SiCOH materials for 45-nm-node Cu interconnects